Avaliação dos efeitos do óleo de cróton como potencial agente em tratamentos estéticos antiage - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
Among the sought-after aesthetic procedures that are low cost are peelings that consist of controlled desquamation of the skin by means of a pro-inflammatory stimulus, either by the acidity of the product applied or by mechanisms different from other agents. With this stimulus, tissue recovery occurs, removal of imperfections such as scars and stains, and aid in rejuvenation by stimulating collagen production. The Hetter formula (FH), which contains Croton oil (OC) and phenol as the main actives, acts on the reticular dermis, therefore considered a deep peeling, but few studies are related and justify the use of Croton oil in the formula. The oil contains specific components such as phorbois esters that have pro-inflammatory action. This work proposes to evaluate the action of OC alone and incorporated in formulations with the purpose of peeling. For this, ten formulations that were applied to pigs (two males and two females) were evaluated and biopsies were taken on days 1, 7 and 21 after application. Microscopy slides were prepared from the biopsies and stained using the hematoxylin and eosin technique to quantify cells, collagen, and fundamental substance. The Picrosirius Red technique was used for the quantification and differentiation of type I and type III collagen, and Masson's Fontana stain for melanin counting. The results were organized into five approaches. In approach 1, samples of the Hetter formula with a 3-month stock solution (FH3) and samples of the undiluted stock solution (SE) were compared with C- (water and Septisol®) and C+ (Hetter formula). The results indicated that FH3 showed lower efficacy than C+, suggesting that the chemical characteristics of the stock solution, after storage, had undergone alteration potentially affecting the expected biological action. SE showed similar results to those observed for C+. In the second approach, samples containing phenol but no OC (SO) and the formula containing OC but no phenol (SF) were evaluated and compared with controls. It was observed that SO and SF did not show results as effective as C+. However, inflammation near the epidermis was determined after the analysis of SF. In approach 3, the action of IOC (intradermal application of OC) and TAT NAN (intradermal application of India ink) were compared with control groups. Intense inflammation produced by IOC and subsequent tissue restructuring with intense collagen production, a characteristic not observed for TAT NAN, was noted in this approach. This data may reinforce that OC has pro-inflammatory and inflammation-modulating activities in peeling, but a method of application allowing OC penetration into the skin is necessary. In approach 4, possible substitutes for phenol, AG (OC with AG) and ATA (OC with ATA), were proposed. The group treated with ATA showed better results than the group after application of the formula with AG. Finally, in approach 5, the action of FH on dark-haired pigs was evaluated, showing a significant reduction in melanin compared to C-, suggesting that FH is not recommended for Fitzpatrick skin types IV-VI due to causing hypopigmentation. Overall, there has been significant advancement in scientific knowledge about the function of OC in peels, demonstrating that the chemical compounds present in the plant matrix composing the formulation are responsible for the pro-inflammatory function and promotion of collagen production. However, their mechanisms should be evaluated, and the search for new, safer, and more stable formulas should continue.
Keywords: Peeling; Ácido tricloroacético; Ácido glicólico; Colágeno; Peeling; Trichloroacetic acid; Glycolic acid; Collagen; CNPQ::CIENCIAS DA SAUDE::FARMACIA